OUTCOMES OF TACE IN PATIENTS WITH HEPATOCELLULAR CARCINOMA LARGER THAN 10 CM - ALI , A; RIAZ , K (Biological and Clinical Sciences Research Journal, 2024)
Hepatocellular carcinoma (HCC) is a prevalent and aggressive liver malignancy, often presenting at advanced stages where surgical resection is not feasible. Transcatheter arterial chemoembolization (TACE) is a minimally invasive treatment modality that has shown promise in managing unresectable HCC, yet its effectiveness for large tumors (>10 cm) remains underexplored. Objective: To evaluate the outcomes of transcatheter arterial chemoembolization in patients with large unresectable hepatocellular carcinoma. Methods: A retrospective, case-control study was conducted in the Department of Interventional Radiology, PKLI, Lahore from September 2022 to September 2024. A total of 45 patients with hepatocellular carcinoma larger than 10 cm, eligible for TACE but refused aggressive treatment were selected as a control group of the study. A total of 50 age, tumor characteristics, and liver function-matched HCC patients who had undergone TACE were selected as the case group of the study. In the 2-3 months follow-up after TACE, tumor response by recorded by ultrasound or AFP assay. Results: The survival rate in cases (10 months, 95% CI: 5.1-14.3 months) was significantly higher than the control group (2 months, 95% CI: 1.05-3.22 months) (p<0.0001). The 1-year survival was 42% and 8% in cases and controls, respectively. The 2-year survival was 23% and 8%, respectively. Univariable analysis shows INR 1.2 or less, total bilirubin less than 1.6 mg/dL, liver reserve, and TACE were significantly associated with survival. Multi-variable analysis showed that INR of 1.2 or less and TACE remained significant for longer survival. Conclusion: TACE is a successful and safe treatment option for unresectable HCC tumors larger than 10 cm.